Proof Concept in The Concept of The Legal State - Situmorang, Boy Kresendo; Sukarmi; Hanif Nur Widhiyanti (Mahadi: Indonesia Journal of Law, 2025)
The evidentiary process plays a crucial role in procedural law, particularly in business competition trials. As a fundamental aspect of legal proceedings, evidence must be properly utilized, presented, and maintained to ensure fairness. Ideally, parties involved should have the broadest possible access to present evidence that strengthens their position. In this context, business competition laws and regulations establish evidentiary mechanisms that serve as guidelines for law enforcers, including the Indonesia Competition Commission (KPPU) and the Commercial Court, to uphold justice effectively. This study aims to examine the evidentiary framework in business competition cases, particularly addressing conflicting norms that impose limitations on the use of evidence. Using a normative legal research method, the study employs literature review and case analysis to qualitatively assess the application of evidentiary principles. The findings highlight the concept of proportional proof in business competition cases, emphasizing the principle of due process of law. The study concludes that evidence in both legal science and business competition cases must adhere to the principle of due process to ensure fairness. Evidentiary procedures at the KPPU and in objection proceedings at the Commercial Court rely on legally recognized forms of evidence, including both direct and indirect evidence, in accordance with prevailing regulations.